Characteristics of young children with developmental delays and their trends over 14 years in Taiwan: a population-based nationwide study. Issue 5 (8th May 2018) - Lai, Der-Chung; Tseng, Yen-Cheng; Guo, How-Ran
Abstract : Objectives: To describe the epidemiological characteristics of developmental delays (DD) at the national level and assess the changes over time. Design: We calculated the incidence rates of DD from 2003 to 2016 and assessed the trends over time. Setting: As dictated by law, local governments in Taiwan are required to register children with DD and provide services. The central government has constructed a national registry with the data from local centres. We analysed the national registry data. Participants: We included children who were under 6 years old, and this population ranged from 1 164 150 to 1 577 443 per year during the study period. All registered cases were certified through a process set forth by law. Primary and secondary outcome measures: We calculated annual incidence rates by age, sex and geographical area, and assessed trends over the study period. Results: The incidence of DD in children under 6 years old displayed an increasing trend over the study period, ranging from 7.0 to 16.3 per 1000 person-years. Boys had higher incidence throughout all 14 years, and the boy-to-girl rate ratios had an increasing trend over time with some fluctuations, ranging from 1.84 (95% CI 1.77 to 1.92) to 1.99 (95% CI 1.93 to 2.06). In addition, rural areas had higher incidence rates, and the rural to urban rate ratios ranged from 0.98 (95% CI 0.94 to 1.03) to 2.00 (95% CI 1.94 to 2.06) without apparent time trends. Girls had a higher proportion of early reporting (<3 years) throughout all years, but the differences in the proportion of early reporting between rural and urban areas were not consistent. Conclusions: Male sex appeared to be a risk factor for DD, which is unlikely to be due to more attention received by boys because girls had a higher proportion of early reporting. We also found that children lived in rural areas appeared to have a higher risk of having DD.